2008
DOI: 10.1093/europace/eun059
|View full text |Cite
|
Sign up to set email alerts
|

Resynchronization of the left ventricular contraction by tailored programming of right and left ventricular pacing

Abstract: A sub-optimal resynchronization is achieved with simultaneous BIV pacing in most patients. A tailored programming of the relative contribution of RV and LV pacing forms the prerequisite for improving CRT results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…On the basis of the results of the pilot study,7 normal intra-LV delay was defined as a value ≤41 ms. The method of evaluating the intra-LV delay and optimising CRT has been described previously 7 8. In the patients randomised to the CRT group, the simultaneous biventricular pacing mode was chosen if the intra-LV delay was within the upper normal limit of 41 ms.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the results of the pilot study,7 normal intra-LV delay was defined as a value ≤41 ms. The method of evaluating the intra-LV delay and optimising CRT has been described previously 7 8. In the patients randomised to the CRT group, the simultaneous biventricular pacing mode was chosen if the intra-LV delay was within the upper normal limit of 41 ms.…”
Section: Methodsmentioning
confidence: 99%
“…Optimal cardiac synchrony can often be achieved by programming the excitation of the RV or the LV fi rst (V -V optimization). Brignole et al (2008) demonstrated that IVCD at baseline was 63 ms, and decreased to 44 ms with CRT. Further V -V optimization by programming the RV or LV fi rst resulted in a decrease in the delay to 26 ms.…”
Section: Optimization Of Crtmentioning
confidence: 96%
“…Further V -V optimization by programming the RV or LV fi rst resulted in a decrease in the delay to 26 ms. In most cases, the LV is activated before the RV (Brignole et al 2008 ). Since it is not clear which V -V interval will be optimal, repeated testing is required.…”
Section: Optimization Of Crtmentioning
confidence: 99%
“…O náročnosti optimalizace svědčí např. to, že autoři jedné z metod založené na měření dyssynchronie pomocí tkáňově dopplerovských technik považují svoji metodu za poměrně rychlou, neboť optimalizace jednoho pacienta netrvala déle než 60 min [5]. Metod k zjišťování a měření vlivu stimulačních intervalů na hemodynamiku ale existuje celá řada.…”
Section: úVodunclassified